ہم جنس پرستی کا معاصر بین الاقوامی رجحان اور اس کے محرکات و اثرات: فکر اسلامی کے تناظر میں ایک تنقیدی جائزہ: Contemporary International Trend of Homosexuality and its Causes and Effects: A critical review in the context of Islamic thought - Haroon, Muhammad; Abrar, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2023)
No one can deny the fact that apart from food and drink, human beings also have sexual desires, and the satisfaction of these desires is also necessary for the human soul. While nature has taught man how to fulfill other needs of life, he has entrusted the method of marriage to fulfill the desires of the self which is not only self-satisfaction but also a high-quality status for the survival of humanity and the start of a family. But a so-called enlightened group of the contemporary age has abandoned this natural method and adopted an unnatural method like homosexuality, which is not only the basis of the moral evils spreading in the society but also the cause of many physical diseases. Moreover, the people who commit this sin also oppose the religious orders because in all the Semitic religions, this act has been declared as haram and a punishable crime, especially Islam has ordered to punish severely for committing this sin. So that people stay away from this sin. Despite knowing and understanding this fact, this epidemic has quickly engulfed many countries and today, not only various European and American countries of the world but also some Eastern nations have declared it legitimate. Although some forces are still strongly opposing to this practice but on the other hand, in many countries, these homosexuals are also taking the lead in legalizing this practice. After the introduction of homosexuality in different societies, what kind of effects have they had and to what extent have these countries given legal protection to homosexuals? Moreover, what is the rate of crime and diseases in these countries and how is the idea of ​​homosexuality affecting all these matters? In addition, among the Semitic religions, how has Islam condemned this sin and what punishment has it ordered for the perpetrators of this sin? This research paper is being written to address all these questions. Keywords: Contemporary, International Trend, Homosexuality, Causes, Effects, Islamic thought.